2018
DOI: 10.1108/ijwis-04-2017-0028
|View full text |Cite
|
Sign up to set email alerts
|

Minimal implications base for social network analysis

Abstract: Purpose Currently, social network (SN) analysis is focused on the discovery of activity and social relationship patterns. Usually, these relationships are not easily and completely observed. Therefore, it is relevant to discover substructures and potential behavior patterns in SN. Recently, formal concept analysis (FCA) has been applied for this purpose. FCA is a concept analysis theory that identifies concept structures within a data set. The representation of SN patterns through implication rules based on FC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…As mentioned in [16], the Impec -most popular algorithm to extract proper implications sets -was proposed in order to extract all proper implications from a formal context, but it does not perform well for larger datasets. A similar algorithm was proposed by [18], named PropIm, which is based on the Impec algorithm, but only identifies proper implications with support greater than zero, meaning all the implications found have at least one occurrence in the dataset. The algorithm was used to identify the relationships between professional skills of LinkedIn user profiles through proper implications.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…As mentioned in [16], the Impec -most popular algorithm to extract proper implications sets -was proposed in order to extract all proper implications from a formal context, but it does not perform well for larger datasets. A similar algorithm was proposed by [18], named PropIm, which is based on the Impec algorithm, but only identifies proper implications with support greater than zero, meaning all the implications found have at least one occurrence in the dataset. The algorithm was used to identify the relationships between professional skills of LinkedIn user profiles through proper implications.…”
Section: Related Workmentioning
confidence: 99%
“…Implications from this set are useful because they provide a minimum data representation -especially for applications that require a minimum set of attributes to reach a specific conclusion. In [18], the authors used the proper implications set to identify relationships between professional skills of LinkedIn users. From the set of proper implications, the authors identified the minimum set of skills (premise) required for a certain professional competence (conclusion).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations